Peran Supervisi Manajerial Dalam Meningkatkan Kualitas Sekolah Di SDN Ibu Dewi 3 Kabupaten Cianjur - Sulis Tyaningsih; Moh. Jailani; Siti Qomariyah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Managerial supervision at school is a necessary measure to ensure that the various teaching activities, administrative aspects, and management of the school can run well. In this context, managerial oversight at school becomes very important because it has several benefits. Managing supervision is an activity designed to improve the management and administrative systems at school. In that way, managing oversight can help improve the quality of education. The aim of this research is to obtain information about the role of managerial supervision in the quality of schools. The research method used is qualitative descriptive with techniques of data collection of interviews, observations and documentation studies. The results of the research concluded that the role of managerial supervision in improving the quality of School in SDN Ibu Dewi 3 Cianjur is the awareness of the administrative staff to improve their quality. School leadership is an important factor in creating a good quality school. A good headmaster can lead and direct teachers, students, and staff well. This can be seen from the headmaster's actions in motivating teachers and staff, improving school management systems, to making good decisions for the good of the school. All these aspects must be taken into account and focused on achieving good quality schools. Then managerial supervision should be done as an attempt to build a quality school.